The (Dis-)equalizing effects of production networks - Leonhard Ipsen; Jan Schulz-Gebhard (Bamberg University, Bamberg Economic Research Group (BERG), 2024)
We suggest and empirically substantiate that the global production network constitutes an important variable for inflation inequality, as it modulates the impact of cost-push shocks on households. For most price shocks, the production network reduces inflation inequality, however, at the expense of lower-income households. Introducing a synthetic Consumer Price Index indicates lower-income households to be at the losing end of the overall effect of supply-side price shocks.
Keywords: 330; Inequality; Inflation; Input-output Analysis; Europe